The Maqasidi Interpretation Approach to Realising Work-Life Balance for Family Welfare - Rizqi, Muhammad Naufal; Ramdani, Rahmatullah; Harun, Harun; Armadi, Ardian Bagus; Muktaz, Muhammad Ubaid Lutfi; Ahmad, Iyas Rounaqy (ZAD Al-Mufassirin, 2025)
This research aims to analyse the application of Tafsir Maqasidi to realising (work-life balance) and improving family welfare based on maqasid al-shariah principles. The research method uses a qualitative approach through a literature study with the main source Al-Qur'an, Hadith, and academic literature. The results show that maqasid al-shariah includes the maintenance of religion (hifz al-din), soul (hifz al-nafs), reason (hifz al-aql), property (hifz al-mal), and offspring (hifz al-nasl) to be the basis for the fair division of husband-wife roles. The husband is responsible as the leader of the family in maintaining religious values, providing for, educating children, and protecting the family from negative influences. Meanwhile, the wife plays a role as a companion to her husband, manager of the household, and the main educator of the children. The collaboration of both parties, supported by flexibility and mutual agreement, creates a harmonious family (sakinah) and a balance between worldly and hereafter responsibilities. This research highlights the importance of integration of Islamic principles in overcoming modern challenges related to work-life balance, while strengthening the role of the family as the main unit of the formation of a moral society.